Podnikatelský záměr rozvoje firmy - Appl, Radek (Vysoké učení technické v Brně. Fakulta podnikatelská, 2015)
Cílem mé práce je sestavení podnikatelského plánu na rozšíření konkrétní malé společnosti v návaznosti na jeho aktuální stav, možný budoucí růst a další rozvoj. V první části mé práce se zaměřím na dostupné zlepšovací procesy, které je možné implementovat do podnikové praxe za účelem inovace stávajících procesů a posunu společnosti na vyšší úroveň. V druhé části shrnu aktuální stav společnosti s možnými podnikatelskými příležitostmi a za pomocí zlepšovacích procesů, navrhnu plán rozšíření společnosti tak, abych zabezpečil stabilní růst společnosti a připravenost všech podnikových systémů a procesů pro další rozvoj, zvýšení hodnoty společnosti i zlepšení hospodářských výsledků.

The aim of my thesis is to create business plan for expansion of concrete small size company in connection to it's current situation, possible future growth and further development. First part of my thesis is focused on available innovation processes, which can be implied to daily work to get desired innovation and improvement of current status and to shift the company to the next level. Second part of my thesis will be summing up the actual status of the company in connection to possible business opportunities and by using the innovation processes I am going to suggest business plan to extend the company in the way it secures stable company's growth and readiness of all business systems and processes for further enlargement, with the aim of increasing company's value even improving operating results.
Entrepreneurial Intention of Business Development
Keywords: Podnikatelský plán; rozšíření podniku; inovace; systém; zlepšování; malý a střední podnik; Business plan; company expansion; innovation; system; improvement; small and medium enterprise